Hukum dan Kebijakan Indonesia Dalam Memerangi Pendanaan Terorisme: Sebuah Analisa Pemutakhiran - Afriansyah, Arie; Ghozi, Ahmad; Wargadalem, M Akila (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2023)
This article discusses Indonesia's latest developments, challenges, and remedies for Anti-Money Laundering (AML) and Counter-Terrorist Financing (CFT) laws. Data were collected by analyzing the challenges of implementing international regulations, such as the United Nations Security Council Resolution (UNSCR) and FATF recommendation. Indonesia is expected to improve their regulations and set high supervision towards the risk of AML/CFT to combat terrorism financing. No studies have been conducted to discuss the latest 2019 UNSCR, a relevant regulation to be implemented by countries to tackle terrorist financing. Therefore, this study aims to examine the significant contribution of the UNSCR and suggest proper implementation in Indonesia.